The Effects of Lateral Meniscus Posterior Root Tear and its Repair on Knee Stability of Internal Rotation and Forward Shift: A Biomechanical Kinematics Cadaver Study - Qi, Yan-Song; Bao, Hu-Ri-Cha; Tao, Li-Yuan; Gu, Pei-Liang; Kong, Chao-Le-Men; Wang, Jun-Chen; Xu, Yong-Sheng (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Lateral meniscal posterior root (LMPR) is an important stabilizer for knee joint, providing the stability during tibia forward shifting and internal rotating. It is still controversial that whether the LMPR should be repaired together with ACL reconstruction. This study aims to investigate the effects of LMPR on knee stability intact ACL. Methods: 8 cadaver knees were used and performed the biomechanical kinematics tests in orders of: (1) Group A: the LMPR was intact; (2) Group B: the LMPR was cut off from its tibial end; (3) Group C: the LMPRT has been repaired. The biomechanical kinematics tests for the stability included: (1) tibia internal rotation stability; (2) tibia anterior shift stability (3) tibia internal rotation stability and anterior shift stability at knee valgus. The internal rotation angles and the anterior displacement of tibia was measured at knee flexion of 0°, 30°, 60° and 90°. Results: Comparing to Group A, the internal rotation angles in Group B were increased significantly at knee flexion of 30° (16.01 ± 0.83, 17.88 ± 1.08, P=0.025), 60° (14.62 ±1.07, 16.31 ±1.29, P=0.041), 90° (12.80 ±1.56, 16.78 ±1.23, P=0.002), and were increased significantly at knee flexion of 60° (14.89±1.47, 17.13±0.88, P=0.011), 90° (14.37±0.58, 16.52±1.07, P=0.037) at knee valgus, the anterior tibia displacements in Group B were increased significantly at knee flexion of 30° (3.67± 0.73, 5.01± 0.64, P=0.015), 60° (3.89±0.42, 4.60±0.51, P=0.024). Comparing to Group B, the internal rotation angles in Group C at knee flexion of 30° (16.84± 1.01, P=0.030), 60° (14.33 ±1.10, P=0.019), 90° (14.14 ±1.15, P=0.021) were decreased significantly, and at knee flexion of 60° (14.68±1.10, P=0.013), 90° (14.38±2.04, P=0.045) at valgus, the anterior displacements in Group C were decreased significantly at knee flexion of 30° (4.54± 0.82, P=0.042), 60° (4.18±0.49, P=0.037). Conclusions: In simulated knee with intact ACL, LMPRT can still lead to the notable internal rotational instability at knee flexion from 30° to 90°, as well as the anterior shift instability at knee flexion from 30° to 60°, while LMPRT repair helps to restore the stability. Our study provided a biomechanical kinematics basis for the operation necessity of LMPRT repair.